Administrative and Legal Principles for Determining the Legal Regime of Using Forestry Resources as an Important Component of Nature-Oriented Complex of Ukraine - О. Ye. Volkov (Bulletin of Kharkiv National University of Internal Affairs)
The author has studied the concept and content of the legal regime in the general sense and through the prism of the sphere of research of the forestry fund of Ukraine.